The performance of gross pollutant traps; Urban area Sungai Klang; Malaysia - Haron S.H.; Sidek L.M.; Munir S.N.U.; Said N.F.M.; Zahari N.M.; Basri H.; Mahmad R.; Dom N.M.; Ismail M.A. (American Institute of Physics Inc., 2023)
The cause of flooding is mainly attributed towards the clogging of drainage system. Gross Pollutant Trap (GPT) installed in the urban area larges helps in trapping the pollutants and litters present in the contacting water. But its efficiency is based on the installation site, and maintenance. Therefore it's very necessary to determine the performance of GPT for different year (2015-2016), so that it will help in assisting the local authorities to make a precise decision in determining the result effectiveness of GPT. The current study was carried out under the River of Life project which is upper part Sungai Klang. The performance of GPT was determined based on wetload trap on GPT and frequencies of maintenance's. The results shows that during raining season, there are no relationship with the total wetload trap into GPT. The results obtained from this study will help in making proper decision for installation and maintenance of GPTs as needed for the rehabilitation of river systems and for the efficient maintenance and operation of GPTs. 2018 Author(s).